Effect of irrigation scheduling and live mulching of cowpea on root characteristics, consumptive use and water use efficiency of upland rice - Aparna, RA; Jayakrishnakumar, V (ORYZA-An International Journal of Rice, 2020)
The field experiment was conducted in the farmer's field, Peringammala, Kalliyoor, Thiruvananthapuram during the Virippu 2017 to study the effect of irrigation scheduling and live mulching with cowpea on root and soil moisture characteristics of upland rice. The results revealed that root characters like root volume, root dry weight and root shoot ratio significantly increased under the irrigation treatment I1 [irrigation at 3 cm depth at 10 mm cumulative pan evaporation (CPE)]. The root length was the highest for rain fed control (I7). Among the mulches, live mulching with cowpea (M2) recorded the highest root length and root shoot ratio. The treatments and their interaction had a significant influence on soil moisture. Irrigation at 3 cm depth at 10 mm CPE, live mulching with cowpea and their interaction recorded the highest consumptive use. The highest water use efficiency was recorded by the treatment irrigation at 2 cm depth at 20 mm CPE (I5) and live mulching withcowpea (M2).